2006
DOI: 10.1212/01.wnl.0000249135.78905.75
|View full text |Cite
|
Sign up to set email alerts
|

Intentional motor phantom limb syndrome

Abstract: A preserved sense of agency provided by intact premotor processes translating intention into action may lead to the vivid feeling of movement in a paralyzed limb, similar to kinesthetic illusions in amputees. The interruption of thalamic afferences may explain the persistence and stability of the phantom by preventing any correction of the mismatch between expected and effective movement. The increased blood oxygen level-dependent (BOLD) signal in the basal ganglia-thalamus-cortex pathway during movement of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 41 publications
(39 reference statements)
3
40
1
Order By: Relevance
“…In amputees, this normal combination of lower-and higher-level processes is disrupted and could be the underlying cause of conscious awareness of the phantom limb. This arrangement of processes was reported by Staub et al [41], who found an increased blood oxygen level dependent (BOLD) signal in the Basal Ganglia-Thalamic-Motor-Cortex loop pathway during imaginary movement of a patient with chronic supernumerary phantom limb, which developed only in association with motor intent directed at a hemiplegicanesthetic upper limb. Staub's finding is analogical to what Ramachandran proposes as the "null" signal hypothesis in the mirror neuron system (MNS), which prevents activity in the MNS from reaching the threshold for conscious awareness [17] or related to what Fitzgibbon et al [42] suggests as the underlying cause in synesthesia for pain.…”
Section: Problem Statementsupporting
confidence: 78%
“…In amputees, this normal combination of lower-and higher-level processes is disrupted and could be the underlying cause of conscious awareness of the phantom limb. This arrangement of processes was reported by Staub et al [41], who found an increased blood oxygen level dependent (BOLD) signal in the Basal Ganglia-Thalamic-Motor-Cortex loop pathway during imaginary movement of a patient with chronic supernumerary phantom limb, which developed only in association with motor intent directed at a hemiplegicanesthetic upper limb. Staub's finding is analogical to what Ramachandran proposes as the "null" signal hypothesis in the mirror neuron system (MNS), which prevents activity in the MNS from reaching the threshold for conscious awareness [17] or related to what Fitzgibbon et al [42] suggests as the underlying cause in synesthesia for pain.…”
Section: Problem Statementsupporting
confidence: 78%
“…Staub et al [60] , using a specific cognitive and fMRI protocol, investigated the clinical and anatomic correlates of chronic SPL, which developed only in association with motor intent directed at a hemiplegic-anesthetic upper limb. They reported that the SPL's movements were associated with increased fMRI responses in motor areas and in the bilateral basal ganglia-thalamus, suggesting an abnormal reorganization within the motor system.…”
Section: Pathogenesismentioning
confidence: 99%
“…3 A functional MRI study in a stroke patient with a complete hemiplegic-anesthetic upper limb, but supernumerary limb revealed regular activation of the primary sensory-motor cortex areas during imagination of the movement of real and phantom hand. 48 The mismatch between a central (cortical) movement sensation and compromised thalamocortical feedback loops for the correction between an expected and effective movement has been considered as a basic neurophysiological mechanism underlying phantom limbs.…”
Section: Supernumerary Phantom Limbs In Scimentioning
confidence: 99%